Rubber composition and tire

JP2025026273APending Publication Date: 2025-02-21BRIDGESTONE CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024025959
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-02-22
Publication Date
2025-02-21

Smart Images

  • Figure 2025026273000001
    Figure 2025026273000001
  • Figure 2025026273000002
    Figure 2025026273000002
Patent Text Reader

Abstract

To provide a rubber composition that exhibits excellent low heat generation properties and contributes to improving sustainability.SOLUTION: A rubber composition comprises: a rubber component (A); a carbon black with a cetyltrimethylammonium bromide specific surface area of 30-110 m2 / g (B); and silica with a cetyltrimethylammonium bromide specific surface area of 200 m2 / g or more (C), where the carbon black (B) contains recovered carbon black, the total content of the carbon black (B) and the silica (C) is 30-80 pts.mass relative to 100 pts.mass of the rubber component (A), and the proportion of the carbon black (B) in the total of the carbon black (B) and the silica (C) is 65 mass% or more and 90 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition and a tire. [Background technology]

[0002] In recent years, under the social demand for energy saving and resource saving, tires with low rolling resistance are required to save fuel consumption of automobiles. In response to such demand, a method is known for reducing the rolling resistance of tires to use a rubber composition with reduced hysteresis loss, i.e., a rubber composition with low heat buildup, for tire components, particularly tread rubber, by reducing the amount of carbon black used or using low-grade carbon black.

[0003] It has also been known to use carbon black and silica in combination in a rubber composition in order to achieve low heat build-up while maintaining predetermined performance (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-249359 A Summary of the Invention [Problem to be solved by the invention]

[0005] The technology of Patent Document 1 reduces heat buildup by using a conjugated diene polymer having a specific structure while using carbon black and silica in combination. In response to this, there is a demand for optimizing the carbon black and silica themselves to achieve low heat buildup.

[0006] Meanwhile, in recent years, from the perspective of social sustainability, there has been a demand for the use of so-called sustainable materials, such as materials derived from biological resources (biomass resources) and materials derived from renewable resources (recycled resources), for the various components used in tires, and there has also been a demand for an improvement in the usage rate of sustainable materials (hereinafter sometimes referred to as the "sustainability rate") for rubber compositions for tire components.

[0007] However, in order to improve the sustainability rate of tires, simply replacing currently used fossil resource-derived materials with sustainable materials in the above-described conventional rubber compositions for tire components may result in a deterioration in low heat generation properties.

[0008] Therefore, an object of the present invention is to provide a rubber composition that is excellent in low heat build-up and can contribute to improving sustainability. Another object of the present invention is to provide a tire that uses such a rubber composition, has excellent low heat build-up properties, and can contribute to improving sustainability. [Means for solving the problem]

[0009] That is, the gist of the rubber composition and tire of the present invention that solve the above problems is as follows.

[0010] [1] A rubber component (A), Cetyltrimethylammonium bromide specific surface area is 30~110m 2 / g of carbon black (B); Cetyltrimethylammonium bromide specific surface area is 200m 2 / g or more of silica (C), The carbon black (B) comprises recycled carbon black, a total content of the carbon black (B) and the silica (C) is 30 to 80 parts by mass based on 100 parts by mass of the rubber component (A); A rubber composition, wherein a proportion of the carbon black (B) in a total of the carbon black (B) and the silica (C) is 65 mass % or more and 90 mass % or less. The rubber composition of the present invention is excellent in low heat build-up properties and can contribute to improving sustainability.

[0011] [2] The rubber composition according to [1], wherein the recycled carbon black is obtained by thermal decomposition of a vulcanized rubber product containing carbon black. In this case, used rubber products can be effectively utilized, which can further contribute to reducing the environmental load.

[0012] [3] The rubber composition according to [1] or [2], wherein the recycled carbon black has an ash content of 20 mass% or less. In this case, the various physical properties required for rubber products such as tires and the quality of the regenerated carbon black are improved.

[0013] [4] The rubber composition according to any one of [1] to [3], wherein the proportion of the recycled carbon black in the carbon black (B) is 50 mass % or more. In this case, it is possible to further contribute to improving sustainability and further improve low heat generation properties.

[0014] [5] The rubber composition according to any one of [1] to [4], wherein the rubber component (A) contains a natural rubber. In this case, in addition to low heat generation, various properties such as fracture resistance and crack resistance can be improved.

[0015] [6] The cetyltrimethylammonium bromide specific surface area of ​​the silica (C) is 210 m 2 / g or more. In this case, the durability such as fracture resistance and crack resistance of the crosslinked rubber (rubber composition) and rubber products such as tires can be further improved.

[0016] [7] A tire using the rubber composition according to any one of [1] to [6]. Such a tire according to the present invention not only has excellent low heat generation properties, but also can contribute to improving sustainability. Effect of the Invention

[0017] According to the present invention, it is possible to provide a rubber composition that is excellent in low heat build-up and can contribute to improving sustainability. Moreover, according to the present invention, it is possible to provide a tire using such a rubber composition, which has excellent low heat generation properties and can contribute to improving sustainability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The rubber composition and tire of the present invention will be described in detail below with reference to examples based on embodiments thereof.

[0019] <Definition> The compounds described herein may be derived in whole or in part from fossil sources, from biological sources such as plant sources, from recycled sources such as used tires, or from a mixture of two or more of fossil sources, biological sources, and / or renewable sources.

[0020] In this specification, the "sustainability rate" refers to the total mass ratio of components derived from biological resources (biomass resources) and components derived from renewable resources (recycled resources) in a target material.

[0021] In this specification, the biological resources (biomass resources) refer to carbon-neutral organic resources derived from living organisms, and include, for example, those stored in the form of starch or cellulose, the bodies of animals that grow by eating plants, and products obtained by processing plants or animals, and are resources other than fossil resources (petroleum, coal, natural gas, etc.). The biological resources may be edible or non-edible, but are preferably non-edible from the viewpoint of not competing with food and of effective resource utilization.

[0022] Specific examples of the biological resources include cellulosic crops (pulp, kenaf, wheat straw, rice straw, waste paper, papermaking residues, etc.), wood, charcoal, compost, food waste, vegetable oil residues, fishery residues, livestock waste, food waste, wastewater sludge, natural rubber, cotton, oils and fats (palm oil, castor oil, cottonseed oil, soybean oil, linseed oil, rapeseed oil, coconut oil, peanut oil, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive ... Examples of the biological resources include crops (corn, wheat, rice, rice husks, rice bran, old rice, potatoes, buckwheat, cassava, sago palm, sugarcane, etc.), bagasse (i.e., the residue after squeezing juice from sugarcane), soybeans, soybean pulp, essential oils (pine oil, orange oil, eucalyptus oil, etc.), pulp black liquor, algae, etc. The biological resources may be processed (i.e., biological resource-derived substances). Examples of the processing methods include biological processing methods that utilize the functions of microorganisms, plants, animals, and tissue cultures thereof; chemical processing methods that utilize acids, alkalis, catalysts, thermal energy, light energy, etc.; physical processing methods such as micronization, compression, microwave processing, and electromagnetic wave processing; and the like. The biological resources may also be extracted and refined from the biological resources or biological resources that have been processed (i.e., biological resource-derived substances). For example, sugars, proteins, amino acids, fatty acids, fatty acid esters, etc., purified from the biological resources can be used. Examples of the sugars include sucrose, glucose, trehalose, fructose, lactose, galactose, xylose, allose, talose, gulose, altrose, mannose, idose, arabinose, apiose, maltose, cellulose, starch, chitin, etc., derived from biological resources. Examples of the proteins include compounds derived from biological resources and formed by linking amino acids (preferably L-amino acids), including oligopeptides such as dipeptides. Examples of the amino acids include valine, leucine, isoleucine, arginine, lysine, asparagine, glutamine, phenylalanine, etc., derived from biological resources, and among these, valine, leucine, isoleucine, arginine, and phenylalanine are preferred.The amino acid may be either an L-amino acid or a D-amino acid, but L-amino acids are preferred from the viewpoints of abundance in nature and ease of availability. The fatty acids include butyric acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, etc., which are derived from biological resources. The fatty acid esters include modified products of vegetable oils, animal oils, and fats and oils derived from biological resources. These biological resources may be contaminated with various materials and impurities.

[0023] In this specification, the term "recycled resources" refers to resources obtained by regenerating (recycling) products that have been used once, or that have been collected without being used, or that have been discarded. For example, recycled resources include resources obtained by regenerating (recycling) used rubber products such as used tires.

[0024] <Rubber composition> The rubber composition according to one embodiment of the present invention (hereinafter, sometimes referred to as the "rubber composition of the present embodiment") is a rubber composition comprising a rubber component (A) and cetyltrimethylammonium bromide having a specific surface area of ​​30 to 110 m 2 Carbon black (B) with a specific surface area of ​​200 m 2 / g or more, the carbon black (B) contains recycled carbon black, the total content of the carbon black (B) and the silica (C) is 30 to 80 parts by mass per 100 parts by mass of the rubber component (A), and the proportion of the carbon black (B) in the total of the carbon black (B) and the silica (C) is 65% by mass or more and 90% by mass or less.

[0025] In the following, the cetyltrimethylammonium bromide specific surface area may be referred to as the "CTAB specific surface area" or simply as "CTAB".

[0026] Generally, heat generation in vulcanized rubber occurs when fillers such as carbon black and silica contained in the vulcanized rubber rub against each other in the rubber, and therefore, in an environment where silica is likely to aggregate, the low heat generation property tends to deteriorate. In contrast, in the present invention, by optimizing the specific surface area and compounding composition of carbon black (B) and silica (C) in the rubber composition as described above, silica (C) having a fine particle size enters the gaps between carbon black (B) particles, and does not affect the aggregation of the particles, and the low heat generation state can be maintained.

[0027] Furthermore, as described above, in the present invention, recycled carbon black is used as the carbon black (B) having the above-mentioned specific surface area. In this regard, it has been surprisingly found that when virgin carbon black (such as carbon black derived from plants) is replaced with recycled carbon black, the low heat generation property tends to improve. Therefore, the rubber composition of the present embodiment can contribute to improving sustainability and can also provide excellent low heat build-up properties.

[0028] (Rubber component (A)) The rubber composition of the present embodiment contains a rubber component (A), which provides rubber elasticity to the composition. The rubber component (A) has a sustainability rate of preferably 30% by mass or more, more preferably 40% by mass or more, more preferably 50% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 100% by mass.

[0029] The rubber component (A) is preferably a rubber derived from biological resources or a rubber derived from recycled resources. Here, the proportion of the monomer components derived from biological resources in 100 mol% of the monomer components constituting the rubber derived from biological resources is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, still more preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be 100 mol%. The proportion of monomer components derived from recycled resources in 100 mol% of monomer components constituting the rubber derived from recycled resources is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 80 mol% or more, still more preferably 90 mol% or more, particularly preferably 95 mol% or more, and may be 100 mol%.

[0030] The rubber component (A) is a component that contributes to crosslinking, and usually has a weight average molecular weight (Mw) of 10,000 or more, preferably 50,000 or more, more preferably 150,000 or more, and even more preferably 200,000 or more, and preferably 5,000,000 or less, more preferably 2,000,000 or less, more preferably 1,500,000 or less, and even more preferably 1,300,000 or less. In this specification, the weight average molecular weight (Mw) of the rubber component (A) can be determined, for example, by converting the weight average molecular weight (Mw) into standard polystyrene based on a measurement value obtained by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMULTIPORE HZ-M manufactured by Tosoh Corporation).

[0031] The rubber component (A) is preferably a diene rubber, and the diene rubber is preferably an isoprene rubber or a butadiene rubber, where the isoprene rubber refers to a rubber containing a unit derived from isoprene as a monomer unit, and the butadiene rubber refers to a rubber containing a unit derived from butadiene as a monomer unit.

[0032] Examples of the isoprene-based rubber include natural rubber (NR), synthetic isoprene rubber (IR), modified natural rubber (modified NR), modified natural rubber (modified NR), and modified synthetic isoprene rubber (modified IR). Examples of the natural rubber (NR) that can be used include those commonly used in the tire industry, such as RSS#3 and TSR20 (e.g., SIR20 and STR20). The origin of the natural rubber (NR) is not particularly limited, and examples of the natural rubber include those derived from Hevea brasiliensis, guayule, and Russian dandelion. Examples of the synthetic isoprene rubber (IR) are not particularly limited, and examples of the synthetic isoprene rubber that can be used include those commonly used in the tire industry, such as IR2200. Examples of the modified NR include deproteinized natural rubber (DPNR) and highly purified natural rubber (UPNR). Examples of the modified NR include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. The modified IR includes epoxidized synthetic isoprene rubber, hydrogenated synthetic isoprene rubber, grafted synthetic isoprene rubber, etc. These isoprene-based rubbers may be used alone or in combination of two or more. Among these, NR is preferred as the isoprene-based rubber.

[0033] The isoprene-based rubber preferably has a sustainability rate of 30% by mass or more, more preferably 40% by mass or more, more preferably 50% by mass or more, still more preferably 60% by mass or more, still more preferably 70% by mass or more, even more preferably 80% by mass or more, still more preferably 90% by mass or more, and particularly preferably 100% by mass. In order to set the sustainability rate of the isoprene-based rubber within the above range, it is preferable to use natural rubber (NR) or a polymer synthesized using isoprene derived from biological resources or isoprene derived from renewable resources as a monomer component. In this case, the synthesized polymer may be a homopolymer of a monomer derived from biological resources, a homopolymer of a monomer derived from renewable resources, a copolymer of a monomer derived from biological resources and a monomer derived from renewable resources, or a copolymer of a monomer derived from biological resources and / or a monomer derived from renewable resources and a monomer derived from a fossil resource (petroleum, etc.).

[0034] The rubber component (A) preferably contains natural rubber. When the rubber component (A) contains natural rubber, it is possible to improve various properties such as low heat buildup and fracture resistance. Furthermore, when the rubber component (A) contains natural rubber, it is possible to improve the sustainability rate.

[0035] The proportion of natural rubber in the rubber component (A) is preferably 60% by mass or more, more preferably 70% by mass or more, from the viewpoint of further improving fracture resistance and crack resistance, and is preferably 95% by mass or less, more preferably 85% by mass or less, from the viewpoint of further improving low heat build-up property.

[0036] Examples of the butadiene rubber include butadiene rubber (BR), aromatic vinyl compound-butadiene copolymer rubber (for example, styrene-butadiene rubber (SBR)), etc. Here, butadiene, which is a raw material for butadiene rubber, is preferably derived from biological resources or recycled resources.

[0037] The rubber component (A) preferably contains a butadiene rubber (BR), which can improve the physical properties of the rubber composition, such as the elongation at break (EB). It is particularly preferable that the rubber component (A) further contains a natural rubber (NR) in addition to the butadiene rubber (BR). By using a combination of a natural rubber and a butadiene rubber as the rubber component (A), the elongation at break (EB) after thermal aging of the rubber composition can be further improved.

[0038] In the rubber composition of the present embodiment, the total amount of styrene in the rubber component (A) is preferably 5% by mass or less, more preferably 3% by mass or less, and may be 0% by mass. If the total amount of styrene in the rubber component (A) is 5% by mass or less, the physical properties of the rubber composition are maintained, and the elongation at break (EB) after thermal aging can be sufficiently improved.

[0039] Examples of the butadiene rubber (BR) include high cis content butadiene rubber, low cis content butadiene rubber, and butadiene rubber containing syndiotactic polybutadiene crystals. Commercially available products can be used as the butadiene rubber (BR), and examples of commercially available butadiene rubbers include products from UBE Elastomers Co., Ltd., ENEOS Materials Corporation, Asahi Kasei Co., Ltd., and Zeon Corporation. These butadiene rubbers may be used alone or in combination of two or more.

[0040] Examples of the aromatic vinyl compound-butadiene copolymer rubber (e.g., SBR) include emulsion-polymerized aromatic vinyl compound-butadiene copolymer rubber (e.g., emulsion-polymerized styrene-butadiene rubber (E-SBR)), solution-polymerized aromatic vinyl compound-butadiene copolymer rubber (e.g., solution-polymerized styrene-butadiene rubber (S-SBR)), and the like. In the aromatic vinyl compound-butadiene copolymer rubber, examples of the aromatic vinyl compound (aromatic vinyl monomer) include styrene, vinylnaphthalene, divinylnaphthalene, and the like. These aromatic vinyl compounds may be used alone or in combination of two or more. Among these, styrene is preferred, and styrene derived from biological resources and styrene derived from recycled resources are particularly preferred. That is, the aromatic vinyl compound-butadiene copolymer rubber is preferably SBR. The styrene may have a substituent. As the aromatic vinyl compound-butadiene copolymer rubber, commercially available products can be used, and examples of the commercially available products include products from Asahi Kasei Corporation, ENEOS Materials Corporation, Nippon Zeon Corporation, Sumitomo Chemical Co., Ltd., and the like. These aromatic vinyl compound-butadiene copolymer rubbers may be used alone or in combination of two or more.

[0041] The butadiene-based rubber has a sustainability rate of preferably 30% by mass or more, more preferably 40% by mass or more, more preferably 50% by mass or more, still more preferably 60% by mass or more, still more preferably 70% by mass or more, even more preferably 80% by mass or more, still more preferably 90% by mass or more, and particularly preferably 100% by mass. In order to make the sustainability rate of the butadiene-based rubber fall within the above range, for example, a polymer synthesized using butadiene derived from biological resources, butadiene derived from renewable resources, aromatic vinyl compounds derived from biological resources (e.g., styrene derived from biological resources), and aromatic vinyl compounds derived from renewable resources (e.g., styrene derived from renewable resources) as monomer components may be used. In this case, the synthesized polymer may be a homopolymer of a monomer derived from biological resources, a homopolymer of a monomer derived from renewable resources, a copolymer of a monomer derived from biological resources and a monomer derived from renewable resources, or a copolymer of a monomer derived from biological resources and / or a monomer derived from renewable resources and a monomer derived from a fossil resource (petroleum, etc.). In addition, the butadiene rubber (B-BR) derived from biological resources (biomass resources) and aromatic vinyl compound-butadiene copolymer rubber derived from biological resources (e.g., styrene-butadiene rubber (B-SBR) derived from biological resources (biomass resources)) include not only rubber obtained by polymerizing butadiene, etc. according to a conventional method, but also rubber obtained by reactions or enzyme reactions caused by microorganisms, plants, animals, and tissue cultures thereof (hereinafter also referred to as "microorganisms, etc.").

[0042] In order to set the sustainability rate of the entire rubber component (A) within the above range, it is preferable to use natural rubber (NR) as the rubber component (A) as described above, or to use a polymer synthesized using monomer components derived from biological resources or monomer components derived from recycled resources as monomer components.

[0043] Generally, materials for rubber compositions for tires (rubber and its monomers, fillers, resins, etc.) require large-scale manufacturing equipment for their production, and are therefore usually produced in large factories in specific regions, and a lot of energy is required for the storage and transportation of raw materials and products. In contrast, materials derived from biological resources (biomass resources) are derived from agricultural products, forests, etc. in each region, and can be produced on a small scale by fermentation of microorganisms and catalytic reactions, so by utilizing products and waste from each region, the energy required for the transportation and storage of raw materials can be reduced, and further the energy required for the transportation and storage of the produced materials to tire factories can also be reduced, which is environmentally friendly. In addition, materials derived from regenerated resources (recycled resources) can be obtained, for example, by dismantling and pyrolyzing used tires to extract materials that constitute tires, such as rubber, fillers, and steel cords. In addition, sulfur can be obtained from biological resources or processed products of biological resources by a method including a desulfurization step of desulfurizing biological resources or processed products of biological resources to remove sulfur-containing substances from the biological resources or processed products of biological resources, a recovery step of recovering sulfur from the desulfurization residue generated in the desulfurization step, and a processing step of processing the recovered sulfur into sulfur for vulcanization (for example, the method described in Japanese Patent Application No. 2022-140390), and materials for rubber compositions for tires can be obtained from various wastes and used items. In this way, by using sustainable materials (materials derived from biological resources or materials derived from recycled resources), it is possible to reduce the overall environmental load in tire manufacturing, such as reducing carbon dioxide emissions (LCCO2) over the entire life cycle, reducing energy consumption (LCE) over the entire life cycle, reducing costs (LCC) incurred over the entire life cycle, and reducing the amount of fossil resources used.

[0044] In addition, when producing the rubber composition, the ratio of the monomer components derived from biological resources, the monomer components derived from renewable resources, and the monomer components derived from fossil resources can be appropriately selected according to the supply situation of biological resources, recycled resources, and fossil resources (e.g., monomer components derived from fossil resources) and / or market demand (e.g., demand for biological resources as food), and the monomer components derived from biological resources, the monomer components derived from renewable resources, and the monomer components derived from fossil resources can be polymerized to obtain rubber derived from sustainable materials (materials derived from biological resources or materials derived from renewable resources) having performance equivalent to that of conventional synthetic rubber. When using monomer components derived from renewable resources, it may be difficult to separate them from monomer components derived from fossil resources due to the manufacturing process of the monomer. In that case, the impact on the environment can be evaluated by adopting the concept of mass balance.

[0045] The ratio of each monomer unit (e.g., unit derived from isoprene, unit derived from butadiene, unit derived from aromatic vinyl compound) in the entire rubber component (A) can be adjusted appropriately depending on the component to which the rubber component (A) is applied. The ratio of each monomer unit in the entire rubber component (A) can be adjusted, for example, by appropriately combining the above-mentioned isoprene-based rubber and butadiene-based rubber. In addition, the ratio of cis-bond units in the butadiene-based units can also be adjusted appropriately depending on the component to which the rubber component (A) is applied. In this specification, the term "monomer unit" refers to a structural unit of a polymer, the term "unit derived from isoprene" refers to a structural unit in a polymer constituted based on the monomer isoprene (including the isoprene unit in natural rubber), the term "unit derived from butadiene" refers to a structural unit in a polymer constituted based on the monomer butadiene, and the term "unit derived from an aromatic vinyl compound" refers to a structural unit in a polymer constituted based on the monomer aromatic vinyl compound. In this specification, the ratio of each monomer unit is measured by NMR.

[0046] The rubber component (A) may contain diene rubbers such as acrylonitrile-butadiene rubber (NBR), chloroprene rubber (CR), butyl rubber (IIR), styrene-isoprene-butadiene copolymer rubber (SIBR), etc., in addition to the above-mentioned isoprene-based rubber, butadiene rubber (BR), and aromatic vinyl compound-butadiene copolymer rubber (e.g., SBR). These rubber components may be used alone or in combination of two or more.

[0047] The rubber component (A) may be modified to introduce a functional group that interacts with a filler such as carbon black or silica. Examples of the functional group include amino, amide, isocyanate, imino, imidazole, urea, ammonium, imide, hydrazo, azo, diazo, carboxyl, nitrile, pyridyl, alkoxy, hydroxyl, oxy, epoxy, ether, carbonyl, oxycarbonyl, silyl, alkoxysilyl, mercapto, sulfide, disulfide, sulfonyl, sulfinyl, and thiocarbonyl groups, and these functional groups may have a substituent. These functional groups may be introduced into the rubber component alone or in combination of two or more. Among these, an amino group, an alkoxy group, and an alkoxysilyl group are preferred, and a substituted amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, and an alkoxysilyl group having 1 to 6 carbon atoms are more preferred.

[0048] The functional group can be introduced, for example, by reacting a compound (modifier) ​​having the functional group with the rubber component. The functional group is a modified functional group having an interactive property with a filler such as silica or carbon black, and examples thereof include a nitrogen-containing functional group, a silicon-containing functional group, and an oxygen-containing functional group. Examples of compounds (modifiers) having a nitrogen-containing functional group include amino group-containing compounds, and examples of compounds (modifiers) having a silicon-containing functional group include silicon halides and hydrocarbyloxysilane compounds. Examples of compounds (modifiers) having an oxygen-containing functional group include alkoxy group-containing compounds, alkylene oxide group-containing compounds, and trialkylsilyloxy group-containing compounds. More specifically, examples of the compounds include those described in International Publication No. 2016 / 194316 and International Publication No. 2019 / 117256. These modifiers may be used alone or in combination of two or more.

[0049] The rubber derived from sustainable materials (materials derived from biological resources or materials derived from renewable resources) can be produced in the same manner as conventional synthetic rubber derived from fossil resources, for example, by using monomer components derived from biological resources or monomer components derived from renewable resources, and, if necessary, monomer components derived from fossil resources. The rubber derived from sustainable materials (particularly rubber derived from biological resources) can also be obtained by reactions with microorganisms or enzyme reactions.

[0050] Regarding the method for preparing rubber derived from biological resources from the above-mentioned biological resources, for example, the method described in JP 2022-179158 A can be used. For example, by using butadiene obtained from biological resources as a monomer component, it is possible to obtain butadiene rubber (B-BR) derived from biological resources (biomass resources), and by using styrene obtained from biological resources and butadiene obtained from biological resources as monomer components, it is possible to obtain styrene-butadiene rubber (B-SBR) derived from biological resources (biomass resources). Here, methods for obtaining B-BR and B-SBR from biological resources include, in addition to artificial polymerization methods, methods of polymerization in vivo, and methods of polymerization with biological enzymes. The molecular weight, branching, microstructure, etc. of the obtained B-BR and B-SBR can be appropriately adjusted by changing the polymerization conditions according to known methods according to the target tire performance.

[0051] As the butadiene obtained from the biological resources, butadiene derived from alkyl alcohols (preferably ethanol and butanol, more preferably butanol), butadiene derived from alkenes (preferably ethylene), and butadiene derived from unsaturated carboxylic acids (preferably tiglic acid) can be suitably used. Two or more of these butadienes may be used in combination. As the styrene obtained from the biological resources, styrene obtained from a plant (preferably a plant belonging to the family Hamamelidaceae, Styraxaceae, or Apocynaceae, more preferably a plant belonging to the genera Liquidamus, Styrax, or Catharanthus, and even more preferably Sweetgum, Styrax rosa, or Catharanthus roseus) or a microorganism (preferably a microorganism belonging to the genera Penicillium or Escherichia, more preferably P. citrinum or transformed E. coli) can be suitably used. Two or more of these styrenes may be used in combination.

[0052] Recently, biomass combinat mainly using bioethanol, bioethylene, etc. are planned, but bioethanol and bioethylene are mainly produced using sugars and / or cellulose as biological resources, and other biological resources such as proteins, lipids, and amino acids cannot be effectively utilized. Furthermore, sugars compete with food, and excessive use of cellulose leads to deforestation. Therefore, it is preferable to use multiple types of monomer components derived from biological resources as the monomer components derived from the biological resources, or to use monomer components derived from biological resources, monomer components derived from renewable resources, and monomer components derived from fossil resources in combination, and further to appropriately adjust the ratio of these monomer components. This makes it possible to effectively utilize a wide range of biological resources and renewable resources such as sugars, proteins, and lipids without relying on one type of biological resource, and to stably supply rubber derived from sustainable materials, and further to consider the environment depending on the situation at the time of production. In addition, when using multiple types of monomer components derived from biological resources, it is preferable to use monomer components derived from different biological resources, i.e., monomer components obtained from different biological resources. Specifically, it is preferable to use a mixture of butadiene derived from multiple types of biological resources with different origins as the butadiene derived from biological resources, and / or to use a mixture of styrene derived from multiple types of biological resources with different origins as the styrene derived from biological resources. This allows multiple types of biological resources to be effectively utilized.

[0053] (Carbon Black (B)) The rubber composition of the present embodiment is a rubber composition having a cetyltrimethylammonium bromide specific surface area of ​​30 to 110 m 2 The carbon black (B) has a CTAB specific surface area of ​​30 m 2 If it is less than 110m / g, durability such as fracture resistance and crack resistance may be deteriorated. 2If the CTAB specific surface area exceeds 50 m / g, the low heat generation property is deteriorated. 2 / g or more, and 2 From the viewpoint of further improving the low heat build-up property, the CTAB specific surface area of ​​the carbon black (B) is more preferably 100 m 2 / g or less, and 2 It is more preferable that the molecular weight is not more than 1 / g. The CTAB specific surface area of ​​carbon black can be measured by a method in accordance with JIS K 6217-3:2001 (method of determining specific surface area - CTAB adsorption method).

[0054] The grade of carbon black (B) is not particularly limited as long as the CTAB specific surface area falls within the above range, and examples thereof include GPF, FEF, HAF, ISAF, and SAF.

[0055] The nitrogen adsorption specific surface area (N2SA) of carbon black (B) is 70m 2 / g or more. The N2SA of carbon black (B) is 70m 2 / g or more, the fracture resistance and crack resistance of the crosslinked rubber (rubber composition) and the tire can be further improved. 2 / g or less. The N2SA of carbon black (B) is preferably 140m 2 / g or less, the dispersibility of the carbon black (B) in the rubber composition can be excellent. The nitrogen adsorption specific surface area (N2SA) of carbon black is determined according to JIS K 6217-2:2017 (ISO 4652:2012).

[0056] The carbon black (B) preferably has a dibutyl phthalate oil absorption (DBP oil absorption) of 70 ml / 100 g or more. When the carbon black (B) has a DBP oil absorption of 70 ml / 100 g or more, the durability of the crosslinked rubber (rubber composition) and the tire, such as fracture resistance and crack resistance, can be further improved. From the viewpoint of the processability of the rubber composition, the carbon black (B) preferably has a DBP oil absorption of 140 ml / 100 g or less. The DBP oil absorption of carbon black is determined according to JIS K 6217-4:2001 (method of determining oil absorption).

[0057] The content of the carbon black (B) is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber is applied, the tire components, the target performance, etc. For example, the content of the carbon black (B) is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component (A).

[0058] In the rubber composition of the present embodiment, the total content of carbon black (B) and silica (C) (described later) is 30 to 80 parts by mass relative to 100 parts by mass of the rubber component (A). If the total content of carbon black (B) and silica (C) is less than 30 parts by mass relative to 100 parts by mass of the rubber component (A), durability such as fracture resistance and crack resistance of the crosslinked rubber (rubber composition) and the tire may deteriorate, and if it exceeds 80 parts by mass, low heat generation property of the crosslinked rubber (rubber composition) and the tire may deteriorate. In addition, the total content of carbon black (B) and silica (C) relative to 100 parts by mass of the rubber component (A) is preferably 50 parts by mass or more, more preferably 55 parts by mass or more, from the viewpoint of further improving the fracture resistance of the crosslinked rubber (rubber composition) and the tire. From the viewpoint of further improving the low heat build-up properties of the crosslinked rubber (rubber composition) and the tire, the total content of the carbon black (B) and the silica (C) per 100 parts by mass of the rubber component (A) is preferably 70 parts by mass or less, and more preferably 60 parts by mass or less.

[0059] Furthermore, in the rubber composition of this embodiment, the ratio of the carbon black (B) to the total of the carbon black (B) and the silica (C) is 65% by mass or more and 90% by mass or less. If the ratio of the carbon black (B) to the total is less than 65% by mass, the low heat generation property of the crosslinked rubber (rubber composition) and the tire may deteriorate. Also, if the ratio of the carbon black (B) to the total is more than 90% by mass, the crack resistance may deteriorate.

[0060] -Recycled carbon black- In the rubber composition of the present embodiment, the carbon black (B) must contain recycled carbon black. In this specification, "recycled carbon black" refers to carbon black obtained by recovering from raw materials that are waste materials that have been recycled. Examples of the waste materials that have been recycled include rubber products (particularly vulcanized rubber products) that contain carbon black, such as used rubber and used tires, and waste oil. "Recycled carbon black" is different from carbon black that is produced directly from raw materials such as hydrocarbons, such as petroleum and natural gas, that is, carbon black that is not recycled. Note that "used" here includes not only carbon black that has been actually used and then discarded, but also carbon black that has been produced but not actually used and then discarded.

[0061] The proportion of the recycled carbon black in the carbon black (B) is preferably 50% by mass or more. In this case, this can further contribute to improving sustainability and can further improve low heat generation. From the same viewpoint, the proportion of the recycled carbon black in the carbon black (B) is more preferably 70% by mass or more, even more preferably 90% by mass or more, and particularly preferably 100% by mass (i.e., carbon black (B) is composed only of recycled carbon black).

[0062] In addition, the recycled carbon black used in this embodiment is preferably obtained by pyrolysis of a vulcanized rubber product containing carbon black. In this case, used rubber products can be effectively utilized, which can further contribute to reducing the environmental load. Furthermore, the recycled carbon black used in this embodiment is preferably obtained from a solid residue generated by pyrolysis of the vulcanized rubber product containing carbon black. When a rubber product containing carbon black is pyrolyzed, a solid residue and a volatile component (oil) are obtained, and the recycled carbon black can be recovered from either of them. However, the recycled carbon black used in this embodiment preferably does not include carbon black recovered from oil.

[0063] The solid residue obtained by pyrolysis of wastes such as used rubber and used tires contains ash in addition to carbon black. Ash is derived from non-volatile components contained in rubber and tires. Therefore, the recycled carbon black obtained from the solid residue has a relatively low carbon black content. On the other hand, in consideration of the various physical properties required for tires manufactured using recycled carbon black, the higher the carbon content in the recycled carbon black, the better. In the recycled carbon black used in this embodiment, the carbon content is preferably 80% by mass or more, more preferably 85% by mass or more, more preferably 87% by mass or more, and even more preferably 89% by mass or more. In the recycled carbon black used in this embodiment, the carbon content is preferably 97% by mass or less. The carbon content is a value that does not include adsorbed moisture.

[0064] Specific examples of ash include zinc oxide, zinc sulfide, silica, iron compounds (iron oxide), calcium oxide, aluminum oxide, and magnesium oxide. In the case of recycled carbon black produced from solid residue obtained by pyrolysis of waste, a certain amount of ash remains even after various processes for removing the ash. In this embodiment, the recycled carbon black is allowed to contain ash. The lower limit of the ash content of the recycled carbon black used in this embodiment may be 0.5% by mass. On the other hand, in consideration of the various physical properties required for rubber products such as tires, the quality of the recycled carbon black, and the like, the ash content of the recycled carbon black is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 5.0% by mass or less. In this specification, the ash content of carbon black is calculated from the mass of unburned components (ash content) obtained by burning carbon black at 550° C.±25° C. to convert it to incineration.

[0065] Reclaimed carbon black can also be obtained from the pyrolysis process of used pneumatic tires. For example, European Patent Application Publication No. 3427975, referring to "Rubber Chemistry and Technology", Vol. 85, No. 3, pp. 408-449 (2012), in particular pp. 438, 440, and 442, describes that it can be obtained by pyrolysis of organic materials at 550-800°C with the exclusion of oxygen, or by vacuum pyrolysis at relatively low temperatures (

[0027] ). Carbon black obtained from such pyrolysis processes usually lacks functional groups on its surface, as mentioned in

[0004] of Japanese Patent No. 6856781 (Comparison of Surface Morphology and Chemistry of Pyrolytic Carbon Black and Commercial Carbon Black, Powder Technology 160 (2005) 190-193).

[0066] The regenerated carbon black may lack functional groups on its surface, or may be treated to include functional groups on its surface. The treatment to include functional groups on the surface of the regenerated carbon black can be carried out by a conventional method. For example, in European Patent Application Publication No. 3173251, carbon black obtained from a pyrolysis process is treated with potassium permanganate under acidic conditions to obtain carbon black having hydroxyl and / or carboxyl groups on its surface. In Japanese Patent No. 6856781, carbon black obtained from a pyrolysis process is treated with an amino acid compound containing at least one thiol group or disulfide group to obtain carbon black with an activated surface. The regenerated carbon black according to the present embodiment also includes carbon black that has been treated to include functional groups on its surface.

[0067] In addition, the thermal decomposition of crosslinked rubber products (vulcanized rubber products) such as used tires can be performed, for example, at a temperature of 650° C. or higher. The recycled carbon black used in this embodiment has a nitrogen adsorption specific surface area (N2SA) of 20 to 150 m 2 / g, and the DBP oil absorption is preferably 50 to 150 ml / 100 g. Note that, as the recycled carbon black in this embodiment, a commercially available product can be used, and an example of such a commercially available product is "PB365" manufactured by Enrestec. PB365 is a recycled carbon black produced by pyrolysis of used tires, and has an N2SA of 73.6 m 2 / g. PB365 also contains about 17% by mass of ash.

[0068] -Carbon black other than recycled carbon black- The rubber composition of the present embodiment may further contain, as the carbon black (B), a carbon black other than the recycled carbon black (virgin carbon black) in addition to the above-mentioned recycled carbon black. Examples of the carbon black other than the recycled carbon black include carbon black derived from plants, and examples of the carbon black derived from plants include those derived from castor oil and rosin oil. The grade of the carbon black is not particularly limited, and examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. As the carbon black other than the recycled carbon black, a commercially available product can be used, and examples of the commercially available carbon black other than the recycled carbon black include products from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Nippon Steel Carbon Co., Ltd., Birla Carbon Co., Ltd., and the like. These carbon blacks may be used alone or in combination of two or more.

[0069] The nitrogen adsorption specific surface area (N2SA) of the carbon black other than the recycled carbon black is not particularly limited and can be appropriately adjusted depending on, for example, the tire category to which it is applied, the tire components, the target performance, etc. For example, the nitrogen adsorption specific surface area (N2SA) of the carbon black other than the recycled carbon black is 20 m 2 / g or more is preferable, and 50m 2 / g or more is more preferable, and 70m 2 / g or more is more preferable, and 90m 2 / g or more is more preferable, and 200m 2 / g or less is preferable, and 150m 2 / g or less is more preferable, and 130m 2 / g or less is more preferable.

[0070] The carbon black other than the regenerated carbon black preferably has a dibutyl phthalate (DBP) oil absorption of 50 to 150 mL / 100 g. The carbon black other than the regenerated carbon black preferably has a dibutyl phthalate (DBP) oil absorption of 50 to 150 mL / 100 g and a nitrogen adsorption specific surface area (N2SA) of 20 to 130 m 2 / g, it is more preferable that the dibutyl phthalate (DBP) oil absorption is 80 to 130 mL / 100 g and the nitrogen adsorption specific surface area (N2SA) is 20 to 60 m 2 It is more preferable that the dibutyl phthalate (DBP) oil absorption is 80 to 130 mL / 100 g and the nitrogen adsorption specific surface area (N2SA) is 20 to 60 m 2 By combining the carbon black having a carbon content of 0.1 to 1.0 g with the recycled carbon black (B), the fracture resistance of the rubber composition can be maintained more reliably.

[0071] (Silica (C)) The rubber composition of the present embodiment is a rubber composition having a specific surface area of ​​200 m 2 / g or more. The silica (C) has a CTAB specific surface area of ​​200 m 2 If the CTAB specific surface area is less than 210 m / g, the durability of the crosslinked rubber (rubber composition) and the tire, such as fracture resistance and crack resistance, may be deteriorated. From the viewpoint of further improving the durability of the crosslinked rubber (rubber composition) and the rubber product such as a tire, such as fracture resistance and crack resistance, the CTAB specific surface area of ​​the silica (C) is 210 m 2 On the other hand, the upper limit of the CTAB specific surface area of ​​the silica (C) is not particularly limited, but at present, it is preferably 300 m 2 No products exceeding / g are available. The CTAB specific surface area of ​​silica can be measured by a method in accordance with ASTM-D3765-80.

[0072] Silica (C) has a specific surface area of ​​200 m 2 / g or more, and examples thereof include wet silica (hydrated silicic acid), dry silica (anhydrous silicic acid), colloidal silica, calcium silicate, aluminum silicate, etc., and among these, wet silica is preferred because it has a large number of silanol groups. These silicas (C) may be used alone or in combination of two or more.

[0073] CTAB specific surface area is 200m 2 The silica (C) having a molecular weight of at least 1000 stoichiometric amounts may be a commercially available product, for example, Zeosil Premium 200MP (trade name) from Solvay.

[0074] The silica (C) has a nitrogen adsorption specific surface area (N2SA) of 50 m 2 / g or more, and 2 / g or more is more preferable, and 150m 2 / g or more is more preferable, and 2 / g or less, and 2 / g or less is more preferable, 2 / g or less is more preferable, 2 It is even more preferable that the molecular weight is not more than 1 / g. In this specification, the nitrogen adsorption specific surface area (N2SA) of silica is a value measured by the BET method in accordance with ASTM D3037-93.

[0075] The ratio of the CTAB specific surface area of ​​the carbon black (B) (carbon black CTAB) to the CTAB specific surface area of ​​the silica (C) (silica CTAB) is preferably in the range of (silica CTAB / carbon black CTAB) = 1.8 or more and 2.5 or less from the viewpoint of further improving durability such as fracture resistance and crack resistance of the crosslinked rubber (rubber composition) and tires, while it is preferably in the range of (silica CTAB / carbon black CTAB) = more than 2.5 and 6.7 or less from the viewpoint of further improving the low heat build-up properties of the crosslinked rubber (rubber composition) and tires.

[0076] (Silane coupling agent) Since the rubber composition of the present embodiment contains silica (C), it is preferable to contain a silane coupling agent in order to strengthen the bond between the silica (C) and the rubber component (A) to further increase the reinforcing property and to improve the dispersibility of the silica (C). Examples of the silane coupling agent include bis(3-triethoxysilylpropyl) tetrasulfide, bis(3-triethoxysilylpropyl) trisulfide, bis(3-triethoxysilylpropyl) disulfide, bis(2-triethoxysilylethyl) tetrasulfide, bis(3-trimethoxysilylpropyl) tetrasulfide, bis(2-trimethoxysilylethyl) tetrasulfide, 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, 2-mercaptoethyl trimethoxysilane, 2-mercaptoethyl triethoxysilane, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, 3-triethoxysilylpropyl-N, Examples of the silane coupling agent include N-dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, 3-trimethoxysilylpropyl benzothiazolyl tetrasulfide, 3-triethoxysilylpropyl benzothiazolyl tetrasulfide, 3-triethoxysilylpropyl methacrylate monosulfide, 3-trimethoxysilylpropyl methacrylate monosulfide, bis(3-diethoxymethylsilylpropyl)tetrasulfide, 3-mercaptopropyldimethoxymethylsilane, dimethoxymethylsilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, dimethoxymethylsilylpropyl benzothiazolyl tetrasulfide, etc. As the silane coupling agent, a commercially available product can be used, and examples of the commercially available silane coupling agent include products from Evonik, Momentive, Shin-Etsu Silicone Co., Ltd., Dow Corning Toray Co., Ltd., Tokyo Chemical Industry Co., Ltd., and Azumax Co., Ltd. These silane coupling agents may be used alone or in combination of two or more.

[0077] The content of the silane coupling agent can be appropriately adjusted depending on, for example, the tire category to which it is applied, the tire components, the target performance, etc. For example, the content of the silane coupling agent is preferably 1 part by mass or more, more preferably 6 parts by mass or more, and even more preferably 8 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, even more preferably 12 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the silica (C).

[0078] Bioethanol can also be used as a raw material for the silane coupling agent. Bioethanol is produced mainly using sugars and / or cellulose as biological resources, and other biological resources such as proteins, lipids, and amino acids cannot be effectively utilized. Furthermore, sugars compete with food, and excessive use of cellulose leads to deforestation. Therefore, it is preferable to use multiple types of monomer components derived from biological resources as the monomer components derived from the biological resources, or to use a monomer component derived from a biological resource, a monomer component derived from a renewable resource, and a monomer component derived from a fossil resource in combination, depending on the supply status of various biological resources, the supply status of renewable resources, the supply status of fossil resources, and market demands (for example, the demand for biomass resources as food). This makes it possible to effectively utilize a wide range of biological resources and renewable resources such as sugars, proteins, and lipids without relying on one type of biological resource, and also to consider the environment depending on the situation during production.

[0079] (resin) The rubber composition of the present embodiment may contain a resin. Examples of the resin include terpene resin, rosin resin, C5 resin, C5-C9 resin, C9 resin, cyclopentadiene resin, aromatic resin, coumarone resin, indene resin, coumarone-indene resin, olefin resin, polyurethane resin, acrylic resin, and the like. These resins may be used alone or in combination of two or more. Among these resins, terpene resin, rosin resin, C5 resin, C5-C9 resin, C9 resin, cyclopentadiene resin, and aromatic resin are preferred, and terpene resin and rosin resin are particularly preferred. Terpene resin and rosin resin are naturally derived sustainable resins, so that they can further reduce the environmental load and can further improve tire performance, such as grip performance on various road surface conditions such as dry road surface, wet road surface, snowy road surface, and frozen road surface. In addition, C5 resin, C9 resin, C5-C9 resin, and cyclopentadiene resin can improve wear resistance and fuel economy in a well-balanced manner, while aromatic resin can improve grip performance, wear resistance, and rubber strength in a well-balanced manner.

[0080] The resin may be hydrogenated, i.e., may be a hydrogenated resin (hydrogenated resin). In addition, the resin may be modified to introduce a functional group that interacts with a filler such as carbon black or silica. Examples of the functional group include an amino group, an amide group, an isocyanate group, an imino group, an imidazole group, a urea group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, an epoxy group, an ether group, a carbonyl group, an oxycarbonyl group, a silyl group, an alkoxysilyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, and a thiocarbonyl group.

[0081] The terpene resin is a solid resin obtained by blending turpentine obtained at the same time when rosin is obtained from pine trees, or a polymerization component separated therefrom, and polymerizing it using a Friedel-Crafts catalyst, and examples of the terpene resin include β-pinene resin and α-pinene resin. The terpene resin also includes terpene-aromatic compound resin, and representative examples of the terpene-aromatic compound resin include terpene-phenol resin and styrene-terpene resin. The terpene-phenol resin can be obtained by reacting terpenes with various phenols using a Friedel-Crafts catalyst, or by further condensing with formalin. The styrene-terpene resin can be obtained by reacting styrene with terpenes using a Friedel-Crafts catalyst. The terpenes as the raw material are not particularly limited, and are preferably monoterpene hydrocarbons such as α-pinene and limonene, more preferably those containing α-pinene, and particularly preferably α-pinene.

[0082] Examples of the rosin-based resin include natural resin rosins such as gum rosin, tall oil rosin, and wood rosin contained in raw pine resin and tall oil. Examples of modified rosin, rosin derivatives, and modified rosin derivatives include polymerized rosin, partially hydrogenated rosin thereof, glycerin ester rosin, partially hydrogenated rosin thereof, and fully hydrogenated rosin thereof, pentaerythritol ester rosin, partially hydrogenated rosin thereof, and polymerized rosin, etc.

[0083] The C5 resins include aliphatic petroleum resins obtained by (co)polymerizing C5 fractions obtained by thermal cracking of naphtha in the petrochemical industry. C5 fractions usually include olefinic hydrocarbons such as 1-pentene, 2-pentene, 2-methyl-1-butene, 2-methyl-2-butene, and 3-methyl-1-butene, and diolefinic hydrocarbons such as 2-methyl-1,3-butadiene, 1,2-pentadiene, 1,3-pentadiene, and 3-methyl-1,2-butadiene.

[0084] The C5-C9 resin refers to a C5-C9 synthetic petroleum resin. Examples of the C5-C9 resin include petroleum-derived C5-C11 Examples of the solid polymers include those obtained by polymerizing the fraction using a Friedel-Crafts catalyst such as AlCl3 or BF3, and more specifically, copolymers mainly composed of styrene, vinyltoluene, α-methylstyrene, indene, etc. As the C5-C9 resin, a resin with a small amount of C9 or more components is preferred from the viewpoint of compatibility with the rubber component. Here, "a small amount of C9 or more components" means that the amount of C9 or more components in the total amount of the resin is less than 50 mass%, preferably 40 mass% or less.

[0085] The C9 resin refers to a C9 synthetic petroleum resin, for example, a solid polymer obtained by polymerizing a C9 fraction using a Friedel-Crafts catalyst such as AlCl3 or BF3. Examples of the C9 resin include copolymers mainly composed of indene, α-methylstyrene, vinyltoluene, etc.

[0086] The cyclopentadiene resin refers to a resin containing a unit derived from a cyclopentadiene monomer as a monomer unit. Examples of the cyclopentadiene resin include a homopolymer of a cyclopentadiene monomer, a copolymer of two or more cyclopentadiene monomers, and a copolymer of a cyclopentadiene monomer and another monomer. Here, examples of the cyclopentadiene monomer include cyclopentadiene, dicyclopentadiene, and tricyclopentadiene, and among these, dicyclopentadiene is preferred, that is, the cyclopentadiene resin is preferably a dicyclopentadiene resin. The dicyclopentadiene resin refers to a resin obtained by polymerizing dicyclopentadiene using a Friedel-Crafts catalyst such as AlCl3 or BF3. Examples of dicyclopentadiene resins include homopolymers of dicyclopentadiene, copolymers of dicyclopentadiene and aromatic monomers, and copolymers of dicyclopentadiene and C9 fractions (vinyl toluene, indene, etc.).

[0087] The aromatic resin refers to a resin containing a unit derived from an aromatic monomer as a monomer unit. Examples of the aromatic resin include a homopolymer of an aromatic monomer, a copolymer of two or more aromatic monomers, and a copolymer of an aromatic monomer and another monomer. Examples of the aromatic monomer include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-methoxystyrene, p-tert-butylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, and p-phenylstyrene; phenolic monomers such as phenol, alkylphenol, and alkoxyphenol; and naphthol monomers such as naphthol, alkylnaphthol, and alkoxynaphthol.

[0088] The softening point of the resin is preferably 30° C. or higher, more preferably 60° C. or higher, more preferably 80° C. or higher, more preferably higher than 110° C., more preferably 116° C. or higher, more preferably 120° C. or higher, more preferably 123° C. or higher, and even more preferably 127° C. or higher. From the viewpoint of processability, the softening point of the resin is preferably 160° C. or lower, more preferably 150° C. or lower, more preferably 145° C. or lower, more preferably 141° C. or lower, and even more preferably 136° C. or lower. In this specification, the softening point of the resin is the temperature at which the ball drops when the softening point defined in JIS K 6220-1:2015 (ISO 28641:2010) is measured using a ring and ball softening point tester.

[0089] As the resin, commercially available products can be used, and examples of commercially available resin products that can be used include products from ENEOS Corporation, Arakawa Chemical Industries, Ltd., ExxonMobil Corporation, Clayton, Yasuhara Chemical Co., Ltd., Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Clayton Polymers, Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., and Taoka Chemical Co., Ltd.

[0090] The content of the resin is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, tire components, target performance, etc. For example, the content of the resin is preferably in the range of 5 to 100 parts by mass, and more preferably in the range of 10 to 60 parts by mass, per 100 parts by mass of the rubber component.

[0091] (rubber powder) The rubber composition of the present embodiment may contain rubber powder. The rubber powder may be obtained by crushing used rubber products such as used tires, and removing reinforcing materials such as steel materials and fibers, dust, glass, sand, stones, etc., as desired, or by preparing a new vulcanized rubber composition to produce rubber powder and crushing it. For example, rubber powder can be obtained from vulcanized rubber by the method described in "Rubber Chemistry And Technology". In the process of crushing vulcanized rubber to obtain rubber powder, mechanical treatment or low-temperature treatment may be used. For example, in the mechanical treatment, various crushing devices such as a cracker mill and a granulator can be used to mechanically crush the vulcanized rubber into fine particles. In the low-temperature treatment, the finely chopped vulcanized rubber is frozen at a very low temperature and then crushed into fine particles. In addition, a magnetic separator or the like can be used to remove steel materials, and an air separator or the like can be used to remove fibers. As the rubber powder, a commercially available product can be used, and examples of the commercially available rubber powder include products from Global Corporation or Nantong Huili Rubber Corporation. From the viewpoint of reducing the environmental load, it is preferable to use rubber powder obtained by crushing used rubber products such as used tires. The rubber powder may be used alone or in combination of two or more kinds.

[0092] The composition of the rubber powder is not particularly limited, and depends on the composition of vulcanized rubber such as used rubber products (used tires) that serve as a raw material. In one embodiment, the rubber powder contains a rubber component, carbon black, silica, etc. The rubber component, carbon black, silica, etc. contained in the rubber powder may be the same as or different from the rubber component, carbon black, silica, etc. contained in the rubber composition of the present embodiment described above.

[0093] The rubber powder has a volume average particle size of preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 200 μm or less, and even more preferably 100 μm or less. The smaller the volume average particle size of the rubber powder, the better, and there is no particular lower limit. In this specification, the volume average particle size is measured by a laser diffraction particle size distribution measuring device, for example, "CAPA500" manufactured by Horiba, Ltd.

[0094] The rubber powder has a 60 mesh sieve residue of preferably less than 1 mass%, more preferably 0.5 mass% or less, and even more preferably 0.1 mass% or less, with no particular lower limit. Also, the rubber powder has an 80 mesh sieve residue of preferably less than 10 mass%, more preferably 1 mass% or less, and even more preferably 0.5 mass% or less, with no particular lower limit. In this specification, the sieve residue is measured in accordance with ASTM D5644-01.

[0095] The rubber powder has an acetone extractable content of preferably 12% by mass or less, more preferably 11% by mass or less, and even more preferably 10% by mass or less, and preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more. In this specification, the acetone extractables in the rubber powder refer to the acetone extractables (%) determined by the acetone extraction method in accordance with JIS K6350.

[0096] The content of the rubber powder is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber is applied, the tire components, the target performance, etc. For example, the content of the rubber powder is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, and is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, more preferably 100 parts by mass or less, more preferably 50 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, and particularly preferably 5 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0097] (liquid softener) The rubber composition of the present embodiment may contain a liquid softener. Here, the "liquid softener" is a compounding agent that is liquid at 25°C (room temperature) and has the effect of softening the rubber composition. The liquid softener is not particularly limited, and examples thereof include oil and liquid polymer, among which oil is preferable. These liquid softeners may be used alone or in combination of two or more.

[0098] The oil is a general term for the extender oil contained in the rubber component and the liquid oil added as a compounding agent of the rubber composition, and examples thereof include vegetable oil, process oil, oil obtained by recycling vegetable oil or process oil, or a mixture thereof. From the viewpoint of reducing the environmental load, the oil is preferably vegetable oil or oil obtained by recycling. Examples of the vegetable oil include palm oil, castor oil, cottonseed oil, soybean oil, linseed oil, rapeseed oil, coconut oil, peanut oil, pine oil, pine tar, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive oil, sunflower oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, tung oil, coconut oil, etc. Examples of the process oil include paraffin-based process oil, aromatic process oil, naphthene-based process oil, etc. The oil may be a commercially available product, and examples of the commercially available oil include products from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., ENEOS Corporation, Orisoi Co., Ltd., H&R Corporation, Toyokuni Oil Mills Co., Ltd., and Nisshin Oillio Group Co., Ltd. These oils may be used alone or in combination of two or more.

[0099] The liquid polymer is preferably a liquid diene polymer. Examples of the liquid diene polymer include liquid styrene-butadiene copolymer (liquid SBR), liquid polybutadiene (liquid BR), liquid polyisoprene (liquid IR), liquid styrene-isoprene copolymer (liquid SIR), liquid styrene-butadiene-styrene block copolymer (liquid SBS block polymer), liquid styrene-isoprene-styrene block copolymer (liquid SIS block polymer), liquid polyfarnesene, and liquid farnesene-butadiene copolymer. These liquid polymers may be hydrogenated, or the terminals or main chains may be modified with functional groups (polar groups). These liquid polymers may be used alone or in combination of two or more.

[0100] The content of the liquid softener is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which it is applied, the tire components, the target performance, etc. For example, the content of the liquid softener is preferably 5 parts by mass or more, and more preferably 10 parts by mass or more, and is preferably 100 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 50 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0101] (Anti-aging agent) The rubber composition of the present embodiment may contain an antioxidant, such as N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD), N,N'-bis(1,4-dimethylpentyl)-p-phenylenediamine (77PD), N,N'-diphenyl-p-phenylenediamine (DPPD), N,N'-bis(1-ethyl-3-methylpentyl)-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline polymer (TMDQ), 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline (AW), and 6-anilino-2,2,4-trimethyl-1,2-dihydroquinoline. As the antiaging agent, commercially available products can be used, and examples of the commercially available antiaging agent include products from Ouchi Shinko Chemical Industry Co., Ltd., Sumitomo Chemical Co., Ltd., Seiko Chemical Co., Ltd., Flexis Co., Ltd., etc. These antiaging agents may be used alone or in combination of two or more.

[0102] The content of the antiaging agent is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which it is applied, the tire components, the target performance, etc. For example, the content of the antiaging agent is preferably 1 part by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2 parts by mass or more, and is preferably 12 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 8 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0103] (wax) The rubber composition of the present embodiment may contain a wax. Examples of the wax include natural waxes such as vegetable wax and animal wax; petroleum waxes such as paraffin wax and microcrystalline wax; and synthetic waxes such as ethylene polymers and propylene polymers. Commercially available waxes can be used, and examples of the commercially available waxes include products from Seiko Chemical Co., Ltd., Nippon Seiro Co., Ltd., Ouchi Shinko Chemical Co., Ltd., and the like. These waxes may be used alone or in combination of two or more.

[0104] The content of the wax is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber is applied, the tire components, the target performance, etc. For example, the content of the wax is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and is preferably 10 parts by mass or less, more preferably 6 parts by mass or less, based on 100 parts by mass of the rubber component.

[0105] (Stearic acid) The rubber composition of the present embodiment may contain stearic acid. Commercially available stearic acid may be used, and examples of the commercially available stearic acid include products from NOF Corp., Kao Corp., Fujifilm Wako Pure Chemical Corp., Chiba Fatty Acid Corp., etc. These commercially available stearic acid products may be used alone or in combination of two or more.

[0106] The content of the stearic acid is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, the tire components, the target performance, etc. For example, the content of the stearic acid is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 6 parts by mass or less, per 100 parts by mass of the rubber component.

[0107] (Zinc Oxide) The rubber composition of the present embodiment may contain zinc oxide (zinc white). The zinc oxide is preferably zinc oxide obtained by recycling. Commercially available zinc oxide may be used, and examples of the commercially available zinc oxide include products from Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., and the like. These commercially available zinc oxide products may be used alone or in combination of two or more. The zinc used for the zinc oxide may be not only zinc bullion, but also zinc obtained from recycled zinc or zinc dross.

[0108] The content of the zinc oxide is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, the tire components, the target performance, etc. For example, the content of the zinc oxide is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 6 parts by mass or less, per 100 parts by mass of the rubber component.

[0109] (sulfur) The rubber composition of the present embodiment preferably contains sulfur. The sulfur may be derived from fossil resources, recycled resources, or materials derived from biological resources. From the viewpoint of reducing the environmental load, it is particularly preferable to use sulfur obtained from waste derived from biological resources. Examples of a method for obtaining sulfur from waste derived from biological resources include the method described in the above-mentioned Japanese Patent Application No. 2022-140390. In addition, the sulfur may be powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, soluble sulfur, etc., which are generally used as crosslinking agents in the rubber industry. As the sulfur, commercially available products can be used, and examples of commercially available sulfur products include products from Tsurumi Chemical Industry Co., Ltd., Hosoi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Co., Ltd., etc. These sulfurs may be used alone or in combination of two or more types.

[0110] The sulfur content is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, tire components, target performance, etc. For example, the sulfur content is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.8 parts by mass or more, and is preferably 8 parts by mass or less, and more preferably 5 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0111] (Vulcanization accelerator) The rubber composition of the present embodiment preferably contains a vulcanization accelerator. The vulcanization accelerator may be derived from fossil resources, recycled resources, or biological resources, but is preferably derived from biological resources from the viewpoint of reducing environmental load. The vulcanization accelerator derived from biological resources can be obtained by the method disclosed in, for example, JP-A-2005-139239. Examples of the vulcanization accelerator include sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazolylsulfenamide (CBS), N,N-dicyclohexyl-2-benzothiazolylsulfenamide, N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-oxyethylene-2-benzothiazolesulfenamide, and N,N'-diisopropyl-2-benzothiazolesulfenamide; 1,3-diphenylguanidine (DPG), 1,3-diphenylguanidine (DPG), and 1,3-diphenylguanidine (DPG). Examples of the vulcanization accelerator include guanidine-based vulcanization accelerators such as o-tolylguanidine and o-tolylbiguanidine; thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole (M) and di-2-benzothiazolyl disulfide (MBTS, DM); and thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrastearylthiuram disulfide, tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N). Commercially available products can be used as the vulcanization accelerator, and examples of the commercially available vulcanization accelerators include products from Ouchi Shinko Chemical Industry Co., Ltd. and Sumitomo Chemical Co., Ltd. These vulcanization accelerators may be used alone or in combination of two or more.

[0112] The content of the vulcanization accelerator is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which it is applied, tire components, target performance, etc. For example, the content of the vulcanization accelerator is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, and is preferably 8 parts by mass or less, more preferably 6 parts by mass or less, and even more preferably 5.5 parts by mass or less, relative to 100 parts by mass of the rubber component.

[0113] (Cellulose nanofiber) The rubber composition of the present embodiment may contain cellulose nanofibers (CNF). The cellulose nanofibers can reinforce the rubber composition by blending them with the rubber composition. The cellulose nanofibers are preferably modified cellulose nanofibers, which are fine fibers made from modified cellulose. The fiber diameter of the cellulose nanofibers is not particularly limited, but is about 3 to 500 nm. The average fiber diameter and average fiber length of the cellulose nanofibers can be obtained by averaging the fiber diameters and fiber lengths obtained from the results of observing each fiber using a scanning electron microscope (SEM), an atomic force microscope (AFM), or a transmission electron microscope (TEM). The cellulose nanofibers can be obtained by defibrating cellulose. The average fiber length and average fiber diameter of the fine fibers can be adjusted by oxidation treatment and defibration treatment.

[0114] The raw material for the cellulose nanofibers is not particularly limited as long as it contains cellulose, and examples thereof include plants (e.g., wood, bamboo, hemp, jute, kenaf, agricultural waste, cloth, pulp (softwood unbleached kraft pulp (NUKP), softwood bleached kraft pulp (NBKP), hardwood unbleached kraft pulp (LUKP), hardwood bleached kraft pulp (LBKP), bleached kraft pulp (BKP), softwood unbleached sulfite pulp (NUSP), softwood bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), recycled pulp, waste paper, etc.), animals (e.g., ascidians), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter)), microbial products, etc. These cellulose raw materials may be used alone or in combination of two or more.

[0115] The content of the cellulose nanofibers is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber is applied, the tire components, the target performance, etc. For example, the content of the cellulose nanofibers is preferably in the range of 1 to 100 parts by mass, more preferably in the range of 5 to 70 parts by weight, and even more preferably in the range of 10 to 40 parts by mass, relative to 100 parts by mass of the rubber component.

[0116] (Porous cellulose particles) The rubber composition of the present embodiment may contain porous cellulose particles. The porous cellulose particles are preferably cellulose particles having a porous structure with a porosity of 75 to 95%, and by compounding them with the rubber composition, the performance on ice can be improved. When the porosity of the porous cellulose particles is 75% or more, the effect of improving the performance on ice is excellent, and when the porosity is 95% or less, the strength of the particles can be increased. The porosity is more preferably 80 to 90%. The porosity of the porous cellulose particles can be calculated by measuring the volume of a certain mass of a sample (i.e., the porous cellulose particles) with a measuring cylinder, calculating the bulk density, and using the following formula. Porosity (%) = {1-[bulk specific gravity of sample (g / mL)] / [true specific gravity of sample (g / mL)]} x 100 Here, the true specific gravity of cellulose is 1.5.

[0117] The particle size of the porous cellulose particles is not particularly limited, but from the viewpoint of abrasion resistance, the average particle size is preferably 1000 μm or less. The lower limit of the average particle size is not particularly limited, but is preferably 5 μm or more. The average particle size is more preferably 100 to 800 μm, and further preferably 200 to 800 μm. The porous cellulose particles are preferably spherical particles having a major axis / minor axis ratio of 1 to 2. By using particles having such a spherical structure, the dispersibility in the rubber composition is improved, which contributes to improving performance on ice and maintaining abrasion resistance, etc. The major axis / minor axis ratio is more preferably 1.0 to 1.5. The average particle size and the long axis / short axis ratio of the porous cellulose particles are obtained as follows: That is, the porous cellulose particles are observed under a microscope to obtain an image, and the long axis and short axis of the particles (when the long axis and short axis are the same, the length in a certain axis direction and the length in an axis direction perpendicular to the long axis) are measured for 100 particles using the image, and the average particle size is obtained by calculating the average value, and the long axis / short axis ratio is obtained by averaging the values ​​obtained by dividing the long axis by the short axis.

[0118] The porous cellulose particles are commercially available from Rengo Co., Ltd. under the name "Viscopearl" and are described in JP-A-2001-323095, JP-A-2004-115284, etc., and these can be suitably used.

[0119] The content of the porous cellulose particles is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber is applied, the tire components, the target performance, etc. For example, the content of the porous cellulose particles is preferably in the range of 0.3 to 20 parts by mass, more preferably in the range of 1 to 15 parts by weight, and even more preferably in the range of 3 to 15 parts by mass, relative to 100 parts by mass of the rubber component.

[0120] (solid fine particles) The rubber composition of the present embodiment may contain solid fine particles. The solid fine particles can improve the performance on ice by blending them with the rubber composition. The solid fine particles preferably have an average particle diameter of 1 μm or more, and more preferably 1000 μm or less, and more preferably 300 μm or less. Examples of the solid fine particles include powders derived from plants such as rice husks, walnut powder, and walnut shells; powders derived from animals such as eggshells (eggshell powder) and bone powder; powders derived from natural minerals such as whitebait; inorganic fine particles such as graphite and zinc oxide whiskers; water-soluble metal salt fine particles such as magnesium sulfate and metal salts of lignin sulfonate; non-metallic fibers such as glass fibers; and the like. Among these, rice husks, walnut shells, eggshells, and whitebait are preferred.

[0121] The content of the solid fine particles is not particularly limited, and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, tire components, target performance, etc. For example, the content of the solid fine particles is preferably in the range of 0.3 to 20 parts by mass, more preferably in the range of 1 to 15 parts by weight, and further preferably in the range of 3 to 15 parts by mass, relative to 100 parts by mass of the rubber component.

[0122] (others) In addition to the above-mentioned components, the rubber composition of the present embodiment may further contain various additives commonly used in the tire industry, such as fillers such as calcium carbonate, talc, alumina, clay, aluminum hydroxide, and mica; organic peroxides; etc. The content of these additives is not particularly limited and can be appropriately adjusted depending on, for example, the tire category to which the rubber composition is applied, the tire components, the target performance, etc., and is preferably in the range of 0.1 to 200 parts by mass per 100 parts by mass of the rubber component.

[0123] (Method of manufacturing rubber composition) The method for producing the rubber composition of the present embodiment is not particularly limited, but for example, the rubber composition can be produced by blending various components appropriately selected as necessary with the rubber component, kneading, heating, extruding, etc. In addition, the obtained rubber composition can be vulcanized to produce a vulcanized rubber.

[0124] The conditions for the kneading are not particularly limited, and various conditions such as the input volume of the kneading device, the rotation speed of the rotor, the ram pressure, the kneading temperature, the kneading time, the type of the kneading device, etc. can be appropriately selected depending on the purpose. Examples of the kneading device include a Banbury mixer, an intermix, a kneader, a roll, etc. that are usually used for kneading rubber compositions.

[0125] The conditions of the heat-in are not particularly limited, and various conditions such as the heat-in temperature, heat-in time, heat-in equipment, etc. can be appropriately selected depending on the purpose. Examples of the heat-in equipment include a heat-in roller machine usually used for heat-in of a rubber composition.

[0126] The extrusion conditions are not particularly limited, and various conditions such as extrusion time, extrusion speed, extrusion device, and extrusion temperature can be appropriately selected depending on the purpose. Examples of the extrusion device include an extruder that is usually used for extruding a rubber composition. The extrusion temperature can be appropriately determined.

[0127] The vulcanization apparatus, method, conditions, etc. are not particularly limited and can be appropriately selected according to the purpose. As the vulcanization apparatus, a molding vulcanizer using a mold used for vulcanizing a rubber composition can be mentioned. As the vulcanization condition, the temperature is, for example, about 100 to 190°C.

[0128] (Application) The rubber composition of the present embodiment can be applied to various constituent members of tires, for example, treads (cap treads, base treads, under treads), cushion rubbers, shoulders, sidewalls, clinches, bead fillers, carcass coating rubbers, insulations, chafers, inner liners, etc., and can also be used for side reinforcing layers of run-flat tires, etc. In addition to tires, the rubber composition of the present embodiment can also be applied to belts such as conveyor belts, rubber crawlers, various hoses, vibration-proof rubbers, seismic isolation rubbers, etc.

[0129] The rubber composition of the present embodiment can be applied to the coating rubber of the belt reinforcing layer. The belt reinforcing layer may be a member formed by, for example, covering reinforcing cords (organic fiber cords) arranged substantially parallel to the tire circumferential direction (for example, at an angle of 0 to 5° with respect to the tire circumferential direction) with a reinforcing layer rubber (elastomer). The belt reinforcing layer can be formed by continuously winding a narrow strip prepared by covering an organic fiber cord with an elastomer in a spiral shape in the tire circumferential direction.

[0130] The organic fiber cord applied to the belt reinforcing layer may be, for example, an organic fiber cord having a breaking strength of 6.5 cN / dtex or more, a breaking elongation of 10% or more, and an elastic modulus at 7% elongation of 6.0 mN / (dtex·%) or more.

[0131] An organic fiber cord having a breaking strength of 6.5 cN / dtex or more, a breaking elongation of 10% or more, and an elastic modulus at 7% elongation of 6.0 mN / (dtex·%) or more has high strength at break, large elongation at break, and a high elastic modulus at 7% elongation. Therefore, when an organic fiber cord with such physical properties is used in a belt reinforcing layer, it is possible to improve the steering stability of the tire while ensuring the plunger durability of the tire.

[0132] The material of the organic fiber cord is not particularly limited, and examples thereof include polyesters such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polyethylene furan dicarboxylate (PEF); nylons such as 6-nylon, 6,6-nylon, 4,6-nylon, and 4,10-nylon; and celluloses such as rayon and lyocell. Among these, polyethylene terephthalate is preferred, that is, the organic fiber cord as the reinforcing material of the belt reinforcing layer is preferably a cord made of polyethylene terephthalate (hereinafter, sometimes simply referred to as "polyethylene terephthalate cord"). The polyethylene terephthalate cord has higher rigidity than commonly used nylon cords and is excellent in improving the plunger durability and steering stability of the tire. In addition, the raw material of the organic fiber cord is not particularly limited, and may be derived from synthetic products, biological products, mechanical recycling derived from crushing, melting, and re-spinning PET products such as PET bottles, or chemical recycling derived from depolymerizing and repolymerizing PET products such as PET bottles.

[0133] The rubber composition of the present embodiment can be applied to the coating rubber of the belt layer. In the belt layer, typically, a plurality of belt cords are arranged in parallel. Such belt cords are generally steel cords. The structure of such belt cords is not particularly limited. However, from the viewpoint of effectively achieving both improved durability and low rolling resistance of the tire, the belt cord may have a 1×N structure (N is an integer of 2 or more) formed by twisting N filaments together, an M+N structure in which N sheath filaments (here, N is an integer greater than 1) are twisted in a spiral shape around M core filaments (here, the core filaments may be twisted or may be bundled without twisting), or a multi-twist structure in which a plurality of the 1×N structure or M+N structure are twisted together. It is also preferable that the cord is a monofilament that is twisted in parallel without being twisted with each other.

[0134] The filaments constituting the belt cord have a diameter of X (mm) and a tensile strength of Y (MPa) that satisfies the following formula: 4000-2000X≦Y≦4500-2000X It is preferable that the above formula is satisfied. By using filaments satisfying the above formula in the belt layer, the strength of the belt layer can be further improved, the plunger level can be improved, and the cut resistance of the tire can be supplemented. Here, the tensile strength of the filament is determined in accordance with the provisions of ISO 17832:2009.

[0135] In the filaments constituting the belt cord, the hardness of the surface layer of the filament is preferably 90 to 110% of the hardness of the inner layer, and particularly preferably 100%, from the viewpoint of fatigue resistance. The hardness can be measured, for example, by Vickers hardness. The surface layer of the filament means a layer from the outermost surface to a depth of 0.01 mm, and the inner layer of the filament is defined as the layer deeper than that. The hardness can be measured in a region 0.005 mm deep from the outermost surface for the surface layer, and 0.04 mm deep for the inner layer.

[0136] There is no particular limitation on the method for producing the filaments constituting the belt cord. For example, the filaments may be obtained by refining iron ore and wire drawing, or by refining scrap iron and wire drawing, or by recycling steel extracted from tires.

[0137] <Tires> A tire according to one embodiment of the present invention (hereinafter, sometimes referred to as "the tire according to the present embodiment") is characterized by using the above-mentioned rubber composition. In other words, the tire according to the present embodiment is characterized by including the above-mentioned rubber composition. Since the tire according to the present embodiment includes the above-mentioned rubber composition, it has excellent low heat generation properties and can contribute to improving sustainability.

[0138] The tire of this embodiment can be manufactured by a normal method using the above-mentioned rubber composition. For example, the tire of this embodiment may be obtained by molding an unvulcanized rubber composition and then vulcanizing it, or by molding a semi-vulcanized rubber that has been subjected to a pre-vulcanization process or the like and then further vulcanizing it, depending on the type of tire to be applied. The tire of this embodiment is preferably a pneumatic tire, and the gas to be filled in the pneumatic tire may be normal air or air with an adjusted oxygen partial pressure, or an inert gas such as nitrogen, argon, or helium. EXAMPLES

[0139] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples and can be modified as appropriate without departing from the gist of the present invention.

[0140] (First evaluation) Rubber compositions of the reference examples and the reference comparative examples were prepared according to the compounding recipes shown in Table 1. For each rubber composition obtained, the total mass ratio of materials derived from biological resources (biomass resources) and materials derived from recycled resources (recycled resources) was calculated to calculate the sustainable material ratio. The results are shown in Table 1.

[0141] Each rubber composition was vulcanized at 145°C for 33 minutes to obtain a vulcanized rubber test piece. The loss tangent (tan δ) of the obtained vulcanized rubber test piece was measured using a viscoelasticity measuring device (spectrometer manufactured by Ueshima Seisakusho) under conditions of a temperature of 60°C, a strain of 1%, and a frequency of 52Hz. The low heat build-up property of Reference Comparative Example 1 was set to 100 and expressed as an index. The results are shown in Table 1. The larger the index value, the better the low heat build-up property.

[0142] [Table 1]

[0143] *1 Low Tg modified SBR: Hydrocarbyloxysilane compound modified styrene-butadiene rubber synthesized by the following method, Tg = -65°C, SP value = 8.65 (cal / cm3 ) 1 / 2 *2 High Tg modified SBR: Modified styrene-butadiene copolymer rubber synthesized by the following method, containing 10.0 parts by mass of oil per 100 parts by mass of rubber component, weight average molecular weight (Mw) = 85.2 x 10 4 , molecular weight 200×10 4 More than 500 x 10 4 Percentage below = 4.6%, shrinkage factor (g') = 0.59 *3 Carbon black: Asahi Carbon Co., Ltd., product name "#78" *4 Recycled carbon black: Enrestec, product name "PB365", ash content = 17% by mass *5 Silica: Tosoh Silica Industries Co., Ltd., product name "Nipsil AQ" *6 Silane coupling agent: Evonik, product name "Si75" *7 Heidilight: Manufactured by Resonac, product name "Heidilight H-43M" *8 Other chemicals: Total amount of sulfur, vulcanization accelerator, retarder, adhesion inhibitor, anti-aging agent, wax, resin, softener. The same ratio is used in the reference comparative example and the reference example.

[0144] [Synthesis method of low Tg modified SBR(*1)] A cyclohexane solution of 1,3-butadiene and a cyclohexane solution of styrene were added to a dried, nitrogen-substituted 800 mL pressure-resistant glass container so that the amount of 1,3-butadiene was 67.5 g and styrene was 7.5 g, and 0.6 mmol of 2,2-ditetrahydrofurylpropane was added, and 0.8 mmol of n-butyllithium was added, and polymerization was carried out at 50 ° C for 1.5 hours. At this time, 0.72 mmol of N,N-bis(trimethylsilyl)-3-[diethoxy(methyl)silyl]propylamine was added as a modifier to the polymerization reaction system in which the polymerization conversion rate was almost 100%, and a modification reaction was carried out at 50 ° C for 30 minutes. Thereafter, 2 mL of a 5 mass % solution of 2,6-di-t-butyl-p-cresol (BHT) in isopropanol was added to stop the reaction, and the mixture was dried according to a conventional method to obtain a modified SBR (low Tg modified SBR). Measurement of the microstructure of the resulting modified SBR revealed that the bound styrene content was 10% by mass, and the glass transition temperature (Tg) was -65°C.

[0145] [Method of synthesis of high Tg modified SBR(*2)] The polymerization reactor was a tank-type pressure vessel with an internal volume of 10 L, an internal height (L) to diameter (D) ratio (L / D) of 4.0, an inlet at the bottom, an outlet at the top, and a jacket for temperature control. 1,3-butadiene, which had been previously dehydrated, was mixed at 17.2 g / min, styrene at 10.5 g / min, and n-hexane at 145.3 g / min. In a static mixer installed in the middle of the piping supplying this mixed solution to the inlet of the reactor, n-butyllithium for inactivating remaining impurities was added at 0.117 mmol / min, mixed, and then continuously supplied to the bottom of the reactor. Furthermore, 2,2-bis(2-oxolanyl)propane as a polar substance at a rate of 0.019 g / min and n-butyllithium as a polymerization initiator at a rate of 0.242 mmol / min were fed to the bottom of the polymerization reactor, which was being vigorously mixed with a stirrer, to continue the polymerization reaction continuously. The temperature of the polymerization solution at the top outlet of the reactor was controlled to be 75°C. When the polymerization was sufficiently stabilized, a small amount of the polymer solution before the addition of the coupling agent was withdrawn from the top outlet of the reactor, and an antioxidant (BHT) was added in an amount of 0.2 g per 100 g of polymer, after which the solvent was removed, and the Mooney viscosity at 110°C and various molecular weights were measured. Next, tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine (abbreviated as "A" in the table) diluted to 2.74 mmol / L as a coupling agent was continuously added to the polymer solution flowing out from the outlet of the reactor at a rate of 0.0302 mmol / min (n-hexane solution containing 5.2 ppm water), and the polymer solution to which the coupling agent was added was mixed by passing through a static mixer to undergo a coupling reaction. At this time, it took 4.8 minutes for the coupling agent to be added to the polymer solution flowing out from the outlet of the reactor, the temperature was 68°C, and the difference between the temperature in the polymerization process and the temperature before the modifier was added was 7°C. An antioxidant (BHT) was continuously added to the polymer solution that had undergone the coupling reaction at 0.055 g / min (n-hexane solution) so that the amount was 0.2 g per 100 g of polymer, and the coupling reaction was terminated. Simultaneously with the antioxidant, oil (JOMO Process NC140 manufactured by JX Nippon Oil & Energy Corporation) was continuously added so that the amount was 10.0 g per 100 g of polymer, and mixed with a static mixer. The solvent was removed by steam stripping to obtain a modified conjugated diene polymer (high Tg modified SBR). It was confirmed that the modified conjugated diene polymer obtained by the above method contained nitrogen atoms and silicon atoms. The modified conjugated diene polymer has a "degree of branching" of 8, which corresponds to the number of branches estimated from the number of functional groups of the coupling agent and the amount added (this can also be confirmed from the value of the shrinkage factor), and has a "number of SiO R residues" of 4, which corresponds to the total number of SiO R contained in one molecule of the coupling agent minus the number of SiO R reduced by the reaction.

[0146] From Table 1, it can be seen that by replacing at least a part of the carbon black (virgin carbon black) among various materials contained in the rubber composition with recycled carbon black, the low heat generation property can be improved. In addition, such replacement also contributes to improving sustainability.

[0147] (Second evaluation) A rubber composition having the compounding recipe shown in Table 2 was prepared according to a conventional method. Next, a tire (tire size: 195 / 65R15) was prototyped using the prepared rubber composition as a tire case rubber, and vulcanized rubber was cut out from the prototype tire. For this vulcanized rubber, tan δ was measured at a temperature of 60°C, a strain of 5%, and a frequency of 15 Hz using a viscoelasticity measuring device (manufactured by Rheometrics Co., Ltd.). The tan δ of Reference Comparative Example 2 was set to 100, and the results were expressed as an index according to the following formula. The results are shown in Table 2. A higher heat buildup index indicates better low heat buildup properties. Heat buildup index = (tan δ of vulcanized rubber of Reference Comparative Example 2 / tan δ of each vulcanized rubber) × 100

[0148] [Table 2]

[0149] *11 Natural rubber: RSS#1 *12 Butadiene rubber: manufactured by ENEOS Material Corporation, product name "BR01" *13 CB-1: Manufactured by Asahi Carbon Co., Ltd., product name "Asahi #55" (CTAB: 31m 2 / g, DBP oil absorption: 26ml / 100g, N2SA: 87m 2 / g) *14 CB-2: Manufactured by Asahi Carbon Co., Ltd., product name "Asahi #65" (CTAB: 70m 2 / g, DBP oil absorption: 42ml / 100g, N2SA: 120m 2 / g) *15 Silica-1: Manufactured by Nippon Silica Industry Co., Ltd., product name "Nipsil AQ" (CTAB: 150m 2 / g) *16 Silica-2: Silica produced by the following manufacturing method (CTAB: 230m 2 / g) *17 Silane coupling agent: Shin-Etsu Chemical Co., Ltd., ABC-856 *18 Vulcanization accelerator: N-cyclohexyl-2-benzothiazolylsulfenamide, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Noccela CZ-G" *19 Antioxidant: N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine, manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Nocrac 6C"

[0150] [Method of producing silica-2 (*16)] 12 L of a sodium silicate solution (SiO2 / Na2O mass ratio of 3.5) having a concentration of 10 g / L were introduced into a 25 L stainless steel reactor. This solution was heated to 80° C. The entire reaction was carried out at this temperature. Sulfuric acid having a concentration of 80 g / L was introduced under stirring (300 rpm, propeller agitator) until the pH reached a value of 8.9.

[0151] A sodium silicate solution (with a SiO2 / Na2O mass ratio of 3.5) having a concentration of 230 g / L was introduced at a rate of 76 g / min and sulfuric acid having a concentration of 80 g / L was introduced simultaneously into the reactor over a period of 15 minutes at a rate set to maintain the pH of the reaction mixture at a value of 8.9. A sol of barely agglomerated particles was thus obtained. The sol was recovered and rapidly cooled using a copper coil through which cold water was circulated. The reactor was quickly cleaned.

[0152] 4 L of pure water were introduced into this 25 L reactor. Sulfuric acid with a concentration of 80 g / L was introduced until the pH reached a value of 4. The simultaneous addition of the cooled sol at a flow rate of 195 g / min and of sulfuric acid (with a concentration of 80 g / L) at a flow rate making it possible to set the pH at 4 was carried out over 40 minutes. An ageing step lasting 10 minutes was carried out.

[0153] Forty minutes after the simultaneous sol / sulfuric acid addition was the simultaneous addition of sodium silicate (the same sodium silicate as in the first simultaneous addition) at a flow rate of 76 g / min over 20 minutes and sulfuric acid (80 g / L) at a flow rate set to maintain the pH of the reaction mixture at a value of 4. After 20 minutes, the acid flow was stopped until a pH of 8 was obtained.

[0154] A new simultaneous addition was carried out over 60 minutes with a sodium silicate flow rate of 76 g / min (the same sodium silicate as in the first simultaneous addition) and a sulfuric acid flow rate (having a concentration of 80 g / L) set to maintain the pH of the reaction mixture at a value of 8. The stirring speed was increased when the mixture became very viscous.

[0155] After this simultaneous addition, the reaction mixture was brought to a pH of 4 with sulfuric acid having a concentration of 80 g / L for 5 minutes. The mixture was aged at pH 4 for 10 minutes. The slurry was filtered and washed under reduced pressure (15% cake solids), and after dilution, the resulting cake was mechanically disintegrated. The resulting slurry was spray dried by a turbine spray dryer to obtain silica-2.

[0156] It is clear from Table 2 that the rubber composition of Reference Example 2 is superior in low heat build-up property compared to the rubber composition of Reference Comparative Example 2.

[0157] Based on the first and second evaluations, it is expected that the rubber composition of the present invention and a tire using the same will have excellent low heat build-up properties and can also contribute to improving sustainability. [Industrial Applicability]

[0158] According to the present invention, it is possible to provide a rubber composition that is excellent in low heat build-up and can contribute to improving sustainability. Moreover, according to the present invention, it is possible to provide a tire using such a rubber composition, which has excellent low heat generation properties and can contribute to improving sustainability.

Claims

1. A rubber component (A); Cetyltrimethylammonium bromide specific surface area is 30-110m 2 / g of carbon black (B); Cetyltrimethylammonium bromide specific surface area is 200m 2 / g or more of silica (C), The carbon black (B) comprises recycled carbon black, a total content of the carbon black (B) and the silica (C) is 30 to 80 parts by mass based on 100 parts by mass of the rubber component (A), A rubber composition, characterized in that a proportion of the carbon black (B) in a total of the carbon black (B) and the silica (C) is 65 mass % or more and 90 mass % or less.

2. 2. The rubber composition of claim 1, wherein the recycled carbon black is obtained by pyrolysis of a vulcanized rubber product containing carbon black.

3. The rubber composition according to claim 1 or 2, wherein the recycled carbon black has an ash content of 20 mass % or less.

4. The rubber composition according to claim 1 or 2, wherein the proportion of the recycled carbon black in the carbon black (B) is 50 mass % or more.

5. The rubber composition according to claim 1 or 2, wherein the rubber component (A) comprises a natural rubber.

6. The silica (C) has a specific surface area of ​​210 m 2 The rubber composition according to claim 1 or 2, wherein the elastic modulus is 1 / g or more.

7. A tire comprising the rubber composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Rubber composition and tire

    JP2013249359A